Determinant of Purchase Willingness of Teh Kota (Gen Z Consumer Survey in Semarang Regency) - Nadia Putri Wulandari; Dewi Widyaningsih; Myra Andriana (International Journal of Economics, Business and Innovation Research, 2026)
Research Objectives: This study looks at how customer experience, motives, reference groups, social class, and payment methods on the purchase willingness of The Kota in Semarang Regency. Research Method: This research uses a quantitative method and follows an explanatory research structure. The research population comprises all Generation Z consumers of The Kota in Semarang Regency. A total of 100 respondents were selected and validated using purposive sampling techniques. Data were collected through an online survey using questionnaires distributed via Google Forms. Using SPSS version 26, a multiple linear regression analysis was carried out. Results: The outcomes indicate that partially customer experience, reference groups, and social class have a positive and significant effect, whereas motives and digital payment do not significantly influence purchase willingness. Simultaneously, customer experience, motives, reference groups, social class, and payment methods have a positive and significant effect on purchase willingness. Implications: It is hoped that the findings will provide information for business actors in establishing more precise and effective marketing strategies for business sustainability. They can also support future researchers in expanding the context, sample size, and input of other variables.